Influence of the sociocultural perspective on the sensory perception of wine consumers in Mexico and Spain - Sánchez, Elena; Oliveras, Ingrid; Romero del Castillo, Maria Roser; Salazar, Angeles (Frontiers in Psychology, 2023)
The increasing globalization of companies and markets, including the wine market, makes this study important to understand a cultural comparative between the sensory perception of wine in Mexico and Spain. Eighty consumers were selected with different consumption habits and hedonic (Acceptance and Simple Preference) and descriptive (Word Association Task and the Check-All-That- Apply (CATA) method) sensory tests were performed. The results revealed that there are differences in the conceptualization of wine in the Word Association Task. Where the Spanish consumers used descriptors related to culture and tradition and were stricter when it came to sensory evaluation. Mexican consumers chose terms about the definition of the product itself. Both populations preferred wines of Spanish origin over those of Mexican origin, especially in the case of red wine. Finally, the results of the CATA method, showed that the attributes that discriminate the two types of wine are due more to the country than to the samples, where the Spanish participants demonstrated more ability to differentiating all wines in terms of visual, olfactory and gustatory aspects.